Optimizing deficit irrigation in Monastrell vines grafted on rootstocks of different vigour under semi-arid conditions - Pascual Romero; Pablo Botía; Elisa Morote; Josefa María Navarro (Agricultural Water Management, 2024)
A progressive irrigation reduction was applied during five years (from 2017 to 2021) by using regulated deficit irrigation (RDI) and partial root-zone drying irrigation (PRD) in field-grown mature Monastrell grapevines grafted on five different rootstocks (140Ru, 1103P 41B, 110R, and 161–49C) in the semi-arid wine-growing region of D.O. Bullas, South-Eastern (SE) Spain. The main goal was to adjust the irrigation volume applied during the growing season for each rootstock depending on the drought tolerance/vigour/productivity of the rootstock. Thus, the annual irrigation volume was progressively reduced (from 104 mm year−1 [2017] to 45 mm year−1 [2018‐2019] and 15 mm year−1 [2020‐2021] in the most drought-tolerant, vigorous, and productive rootstocks [1103P, 140Ru], and from 104 mm year−1 [2017] to 74 mm year−1 [2018‐2019] and 58 mm year−1 [2020‐2021] in the less drought-tolerant, vigorous, and productive rootstocks [110R, 161–49C, 41B]. A severe reduction of the irrigation in 140Ru and 1103P substantially reduced vigour, productivity, and berry weight and increased water productivity (WP) (220% and 97%, respectively) and phenolic berry quality (50% and 92%, respectively). Medium/low-vigour rootstocks also had a decrease in vigour, yield, and berry weight in response to an irrigation reduction, enhancing WP (between 17% [41B] and 41% [161‐49C] and phenolic berry quality (between 11% [161–49C] and 46% [110R] With a low water volume DI (53–77 mm year−1), vines grafted on 161–49C delivered the highest berry quality compared to other rootstocks. Physiological changes produced by very low water volume PRD were reflected in a reduced root water and nutrient uptake and leaf gas exchange and a slightly increased technological berry quality compared to RDI. However, PRD did not produce a significant improvement in WP, phenolic concentration, and global berry quality compared to RDI.